OPPORTUNITIES AND CHALLENGES FOR ISLAMIC FINANCIAL TECHNOLOGY DEVELOPMENT IN INDONESIA: LITERATURE STUDY - Andri Soemitra; Rukiah Rukiah; Heri Ansyah Panjaitan; Angga Syahputra (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2021)
The development of digital technology has entered the financial sector which encourages the birth and development of financial technology. The low level of financial literacy coupled with difficulties in accessing financing to the banking sector tends to encourage people to seek alternative financing outside of banking. One of the most developed financial services is financial technology. However, the experience of people using financial technology products shows that there are fundamental problems, especially when people use illegal financial technology products. Therefore, Islamic financial technology is an alternative because Islamic fintech applies the noble values ​​of Islamic teachings. This article was written to review the literature that has been published in scientific journals in the last 4 years that discusses the opportunities and challenges of Islamic financial technology. The results of this study indicate that there are several opportunities and challenges faced by Islamic financial technology companies.